2020
DOI: 10.1080/16078454.2020.1735670
|View full text |Cite
|
Sign up to set email alerts
|

WT1 overexpression predicted good outcomes in adult B-cell acute lymphoblastic leukemia patients receiving chemotherapy

Abstract: Objectives: The prognostic role of WT1 in acute lymphoblastic leukemia (ALL) is still controversial. No study has focused on the prognostic role of WT1 expression in adult BALL patients receiving chemotherapy only. Methods: Using TaqMan-based real time quantitative PCR (RQ-PCR), we detected the WT1 transcript levels of 162 de-novo adult BALL patients at the time of diagnosis and analysed their clinical features. Results: WT1 overexpression was defined as a transcript level higher than 0.50%, which is the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In this study, children with WT1 overexpression had distinctive clinico-biological features, with WT1 overexpression taking place more frequently in the KMT2A-r + subgroup or the Pro-B subgroup or elder children. These findings are in consonance with the outcomes of previous studies ( 3 , 4 , 11 ). According to the study of Boublikova L et al ( 11 ), WT1 overexpression tended to occur in pediatric ALL with KMT2A-AFF1 + or initial age ≥10 years.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, children with WT1 overexpression had distinctive clinico-biological features, with WT1 overexpression taking place more frequently in the KMT2A-r + subgroup or the Pro-B subgroup or elder children. These findings are in consonance with the outcomes of previous studies ( 3 , 4 , 11 ). According to the study of Boublikova L et al ( 11 ), WT1 overexpression tended to occur in pediatric ALL with KMT2A-AFF1 + or initial age ≥10 years.…”
Section: Discussionsupporting
confidence: 93%
“…According to the study of Boublikova L et al ( 11 ), WT1 overexpression tended to occur in pediatric ALL with KMT2A-AFF1 + or initial age ≥10 years. Qin YZ et al ( 3 ) and Wang S et al ( 4 ) also reported that, in adult BCP-ALL, the WT1 transcript levels in the KMT2A rearrangement group were uniformly higher. However, a previous study with a small sample ( n = 40) of pediatric ALL by Hagag A et al ( 7 ) showed a remarkably older age in the negative WT1 gene expression group in comparison with the positive group, but with no essential differences between the two groups regarding other clinical presentations.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The previous study found that WT1 transcription factor (WT1) can play a role in heart and blood vessel formation [38]. It was also regarded as a key element in acute myeloid leukemia [39], and WT1 overexpression was an independent positive prognostic factor in adult B-cell acute lymphoblastic leukemia patients [40]. The transcription factor Sp1 (Sp1) can regulate the expression of multiple genes [41], which can play a role in the body's antioxidant stress [42].…”
Section: Discussionmentioning
confidence: 99%